2020
DOI: 10.1021/acs.energyfuels.0c01522
|View full text |Cite
|
Sign up to set email alerts
|

Probing Aggregation Tendencies in Asphaltenes by Gel Permeation Chromatography. Part 1: Online Inductively Coupled Plasma Mass Spectrometry and Offline Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: This study probes the nanoaggregation behavior of asphaltenes by gel permeation chromatography (GPC). Compounds containing sulfur, vanadium, and nickel were monitored online with elemental detection by inductively coupled plasma mass spectrometry (ICP-MS), and four fractions that vary in nanoaggregation state were analyzed by positive atmospheric pressure photoionization 9.4 T Fourier transform ion cyclotron resonance mass spectrometry ((+)APPI FT-ICR MS). We also highlight some of the challenges associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 44 publications
3
45
0
Order By: Relevance
“…As discussed above, "tailing" species may also experience adsorption on the stationary phase and therefore elute after the full permeation volume. The global compositional trends are consistent with the results reported by Putman et al, 63,69 who concluded that the most abundant species in larger aggregates (e.g., MMW) contain more carbon atoms in alkyl-side chains, suggesting that London forces may be fundamental in asphaltene selfassociation. Several reports 22,86−89 suggest extensive trapping/occlusion of porphyrins within asphaltene aggregates, which is consistent with the abundant detection of vanadiumcontaining compounds in large/sizable aggregates in this work.…”
Section: ■ Experimental Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…As discussed above, "tailing" species may also experience adsorption on the stationary phase and therefore elute after the full permeation volume. The global compositional trends are consistent with the results reported by Putman et al, 63,69 who concluded that the most abundant species in larger aggregates (e.g., MMW) contain more carbon atoms in alkyl-side chains, suggesting that London forces may be fundamental in asphaltene selfassociation. Several reports 22,86−89 suggest extensive trapping/occlusion of porphyrins within asphaltene aggregates, which is consistent with the abundant detection of vanadiumcontaining compounds in large/sizable aggregates in this work.…”
Section: ■ Experimental Methodssupporting
confidence: 90%
“…Conversely, analysis of the later-eluting fractions (less aggregated asphaltenes/free molecules) revealed abundant alkyl-depleted/low-molecular-weight PAHs. In another work, Putman et al 63 performed off-line FT-ICR MS characterization of GPC asphaltene fractions and observed that earlier-eluting compounds were more aliphatic, with MSderived H/C ratios above 1.2. In contrast, later-eluting fractions revealed abundant highly-aromatic/alkyl-depleted species (H/C < 1.0).…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, all MS-based techniques are limited because of selective ionization, ion suppression, and matrix effects. Currently, there is not a “universal” ion source that allows for ionization of complex mixtures without any discrimination toward specific compound classes and structures. Therefore, prior sample fractionation is critical to achieving more complete molecular characterization of complex samples such as asphaltenes. …”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the UV spectroscopy behavior. Putman et al [33] has reported limitations in MS characterization of asphaltenes due to low ionization efficiency of specific chromatography fractions. In this work, according to Table 3 and molecular formulas; such compounds could be completely "free" or present on the aggregate surface and therefore available for MS analyses.…”
Section: Discussion (829 Words)mentioning
confidence: 99%